2020
DOI: 10.3389/feduc.2020.00146
|View full text |Cite
|
Sign up to set email alerts
|

OER4Schools: Outcomes of a Sustained Professional Development Intervention in Sub-Saharan Africa

Abstract: Sustaining educational initiatives beyond short-term pilot projects is highly challenging in low-income countries. We describe the outcomes and implications of our iterative Design-Based Implementation Research conducted in Zambia. This focused on a unique, school-based, peer-facilitated professional learning programme for primary teachers: OER4Schools integrates interactive pedagogy, open digital educational resources and mobile learning. Teacher interviews carried out 18 months after a year-long intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It was run in 12 classes over a school year in one main primary school with limited remote support for the facilitator which faded over time (Hennessy et al, 2016a). A follow-up study 18 months later demonstrated sustainability of the new pedagogical practices without any support from the research team, plus spontaneous extension of the approach to the whole school by peer facilitators (Haßler et al, 2020). Key to the sustainability and further evolution were the balance between a structured programme and supporting teachers' agency to develop and implement classroom practices.…”
Section: Professional Learning Approaches For Supporting Dialoguementioning
confidence: 99%
“…It was run in 12 classes over a school year in one main primary school with limited remote support for the facilitator which faded over time (Hennessy et al, 2016a). A follow-up study 18 months later demonstrated sustainability of the new pedagogical practices without any support from the research team, plus spontaneous extension of the approach to the whole school by peer facilitators (Haßler et al, 2020). Key to the sustainability and further evolution were the balance between a structured programme and supporting teachers' agency to develop and implement classroom practices.…”
Section: Professional Learning Approaches For Supporting Dialoguementioning
confidence: 99%
“…Opportunities to stay with such new surprising insights can be supported by fit-for-purpose assessment tools, structured peer facilitation (Hassler et al, 2018) and organisational routines that create regular spaces for self-reflection, working out changes in practice and stabilising those changes over time (Sherer & Spillane, 2011). In order to effectively facilitate generative dialogues and stabilisation of new practices, however, such organisational routines need to be enriched through collaboration and trialling tools (Dickens, 2021;Hassler et al, 2020;Marfan, 2021;Rainio & Hofmann, 2021). We next discuss some examples.…”
Section: Facilitating Teacher Noticing Regarding Students' Unexpected Learning Gaps and Gainsmentioning
confidence: 99%